A mixture design study to determine interaction effects of wheat, buckwheat, and rice flours in an aqueous model system - Yilmaz, Mustafa Tahsin; Yildiz, Onder; Yurt, Bayram; Toker, Omer Said; Karaman, Safa; Basturk, Ayhan (ELSEVIER SCIENCE BV, 2015)
Mixture design approach was used to study effects of interactions between wheat, buckwheat and rice flours on pasting and textural properties of an aqueous model system. Each flour type had a marked effect on these properties, but their interaction effects were more remarkable on pasting properties, furthermore reversing the way of linear effects on textural properties. The results of this study revealed that buckwheat and rice flours should be used as a combination in the baking formulations when lower breakdown viscosity values are requested. It was also found that the use of rice flour with buckwheat flour as a combination increased viscosity of the flour mixture, but decreased retrogradation and syneresis rate. On the other hand, use of wheat flour in combination with buckwheat flour resulted in lower hardness, gumminess, chewiness and resilience in the flour mixture. These results revealing the interaction effects should suggest very advantageous findings for baking industry because they would have an opportunity to have a free hand in controlling these texture profile analysis (TPA) parameters in accordance with their purposes by considering these interaction results. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Wheat; Buckwheat; Rice; Pasting; Mixture design; PASTING PROPERTIES; AMYLOSE CONTENT; GLUTEN; QUALITY; PRODUCTS; STARCH; PROTEIN; BREAD; BEHAVIOR; Food Science & Technology